2019
DOI: 10.3390/genes10121049
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Mammalian Genome within Phase-Separated Nuclear Bodies: Experimental Methods and Implications for Gene Expression

Abstract: The importance of genome organization at the supranucleosomal scale in the control of gene expression is increasingly recognized today. In mammals, Topologically Associating Domains (TADs) and the active/inactive chromosomal compartments are two of the main nuclear structures that contribute to this organization level. However, recent works reviewed here indicate that, at specific loci, chromatin interactions with nuclear bodies could also be crucial to regulate genome functions, in particular transcription. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…The intergenic leading enhancers (I12a, I56i, and I37-2) and the distal leading enhancers (URE2, eDlx#18, eDlx#19, and mU4-Tad3) are physically located relatively close by CTCF-cohesin loop (Figure 4). Upon activation, transcription factors (TFs) accumulate on the leading enhancers and could form small seeds of phase-separated molecular condensates consisting of TFs and co-activators (Hnisz et al, 2017, Shin et al, 2018, Lesne et al, 2019.…”
Section: How Do Multiple Enhancers Work? -Putative Scenario For DLX Gene Activation Process Depending On the Long-range Distal Enhancersmentioning
confidence: 99%
“…The intergenic leading enhancers (I12a, I56i, and I37-2) and the distal leading enhancers (URE2, eDlx#18, eDlx#19, and mU4-Tad3) are physically located relatively close by CTCF-cohesin loop (Figure 4). Upon activation, transcription factors (TFs) accumulate on the leading enhancers and could form small seeds of phase-separated molecular condensates consisting of TFs and co-activators (Hnisz et al, 2017, Shin et al, 2018, Lesne et al, 2019.…”
Section: How Do Multiple Enhancers Work? -Putative Scenario For DLX Gene Activation Process Depending On the Long-range Distal Enhancersmentioning
confidence: 99%
“…To investigate the role played by LLPS in spatial genome organization, we used human HeLa cells that were treated with 1,6-HD. This aliphatic alcohol is predicted to disrupt weak hydrophobic interactions, both in vitro and in vivo, disassembling LLPS-dependent macromolecular condensates (Kroschwald et al 2017;Alberti et al 2019;Lesne et al 2019).…”
Section: 6-hd Treatment Of Living Cells To Study Higher-order Chrommentioning
confidence: 99%
“…Molecular condensates depended purely on phase separation driven by electrostatic interactions are expected to be unaffected by 1,6-HD treatment (Lesne et al 2019). Nevertheless, 1,6-HD is the only available tool to test in vivo the contribution of LLPS in the assembly of macromolecular assemblies at this moment (Kroschwald et al 2017).…”
Section: 6-hd Treatment Of Living Cells To Study Higher-order Chrommentioning
confidence: 99%
“…Subsequent Hi-C studies with greater resolution further divided the compartments into six different sub-compartments with distinct histone marks and epigenetic properties [15]. It is therefore speculated that the compartmentalisation is mediated by the similar physical properties of different chromatin states, possibly via phase separation [27][28][29][30][31] (Figure 1B). In support of this, several studies have demonstrated HP1α and other heterochromatic H3K9me3 recognition complexes are able to form phase-separated liquid droplets, containing other macromolecules, such as DNA [29,32,33].…”
Section: Introductionmentioning
confidence: 99%